Ethnoveterinary Survey Conducted in Baiku Yao Communities in Southwest China - Luo, Binsheng; Hu, Qimin; Lai, Kedao; Bhatt, Arvind; Hu, Renchuan (Frontiers in Veterinary Science, 2022)
Baiku Yao is a branch of the Yao ethnic group mainly living in Guangxi and Guizhou provinces of China. They are recognized by UNESCO as an ethnic group with an intact ethnic culture. The Baiku Yao people have extensive ethnoveterinary knowledge, which they used to prevent and control various animal diseases. During the African swine fever outbreak, the livestock of the Baiku Yao community remained unaffected. We investigated ethnoveterinary knowledge among local Baiku Yao villagers. A total of 39 ethnoveterinary plant species are utilized for the treatment of various diseases. Five species, namely, Stephania kwangsiensis, Aristolochia kwangsiensis, Clerodendrum bungei, Paederia foetida, and Tetradium ruticarpum, had the highest relative frequency values. Strobilanthes cusia, Tetradium ruticarpum, and Stephania kwangsiensis are highly valued locally for treating animal plagues. The existing traditional ethnoveterinary knowledge needs to be conserved and validated scientifically.